2023
DOI: 10.3390/math11061515
|View full text |Cite
|
Sign up to set email alerts
|

Validity Evidence for the Internal Structure of the Maslach Burnout Inventory-Student Survey: A Comparison between Classical CFA Model and the ESEM and the Bifactor Models

Abstract: Academic burnout is a psychological problem characterized by three dimensions: emotional exhaustion, depersonalization, and personal accomplishment. This paper studies the internal structure of the MBI-SS, the most widely used instrument to assess burnout in students. The bifactor model and the ESEM approach have been proposed as alternatives, capable of overcoming the classical techniques of CFA to address this issue. Our study considers the internal structure of the MBI-SS by testing the models most frequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 67 publications
1
5
0
Order By: Relevance
“…These results are in line with the findings of Aguayo-Estremera et al (2023) , which showed that whereas the three-factor congeneric model did not reach adequate global fit indices, the bifactor model fitted the data well. Despite these results, Aguayo-Estremera et al (2023) did not advocate for a unidimensional factor structure of the MBI because of two reasons: In the first place, a good fit for the bifactor model does not imply evidence for unidimensional structures; in the second place, they fitted a three-factor model using Exploratory Structural Equation Modeling (ESEM) that obtained excellent global fit indices. The difference between CFA and ESEM is that in the latter cross-loadings are specified in the model, allowing a better model fit in the case of relevant cross-loadings.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results are in line with the findings of Aguayo-Estremera et al (2023) , which showed that whereas the three-factor congeneric model did not reach adequate global fit indices, the bifactor model fitted the data well. Despite these results, Aguayo-Estremera et al (2023) did not advocate for a unidimensional factor structure of the MBI because of two reasons: In the first place, a good fit for the bifactor model does not imply evidence for unidimensional structures; in the second place, they fitted a three-factor model using Exploratory Structural Equation Modeling (ESEM) that obtained excellent global fit indices. The difference between CFA and ESEM is that in the latter cross-loadings are specified in the model, allowing a better model fit in the case of relevant cross-loadings.…”
Section: Discussionsupporting
confidence: 90%
“…However, this conclusion does not necessarily lead to rejecting a three-dimensional structure as proposed by the original authors ( Maslach and Jackson, 1981 ). As obtained previously ( Aguayo-Estremera et al, 2023 ), evidence for a three-factor model might be obtained when controlling for cross-loadings using Exploratory Structural Equation Modeling (ESEM). Likewise, we can state that the one-factor model is not a proper representation of the MBI internal structure since fit indices for this model were poor.…”
Section: Discussionmentioning
confidence: 61%
“…Alpha and omega reliability coefficients together with their corresponding 95% confidence interval were calculated for each dimension of the CBG-USS and MBI-SS, taking as reference for the evaluation of the reliability coefficients the recommendations made in this regard by George and Mallery [56] and Aguayo et al [57].…”
Section: Discussionmentioning
confidence: 99%
“…Another widespread mental health issue in society is related to the work environment. The burnout syndrome is related to prolonged exposure to stressors, and it has traditionally been characterized by emotional exhaustion, depersonalization, and low personal accomplishment [19], although models with a different number of factors have also been explored [20]. Factors such as job changes, stress, caregiver burden, unrealistic expectations, and personal relationships have been studied as possible causes of the syndrome [21], as well as personality factors [22].…”
Section: Mental Health Stigma and Addictive Behaviorsmentioning
confidence: 99%